Anzianità e Anziani per i Testimoni di Geova - Botti, Federica (De senectute, 2023)
The term Elders in Jehovah’s Witnesses is not only used for older people, but also applies in a special way to those who hold a position of authority and responsibility, since Elders are also the ministers of worship of this religious denomination. This research aims to highlight the different meanings of the term Elder in the doctrine of Jehovah’s Witnesses and how they find their place in the Italian legal system.